A cura da mulher hemorrágica:um diálogo entre a teologia e a medicina a partir de uma leitura de Lucas 8.43-48 - Queiroz, Lauro José Coelho (2014)
This paper proposes a dialog between theology and medicine based on the analysis of the cure of the woman suffering from hemorrhages (Lk 8:43-48). The research is guided by the exegetical and methodological practice of Faculdades EST and its research orientators. The work describes in a brief way, the issue of the meaning of curing in the context of the first century, the history of medicine, presenting its concept and its origin, as it applies to what illness meant to the primitive people of Mesopotamia and to illness in the East, in Greek mythology and the development of medicine in Greece, Roman medicine and medicine among the Hebrew people. It also deals with the author of the Gospel which the tradition of the church attributes to Luke, the doctor, originally from Syrian Antioch, with the illness which plagued the woman in Luke 8:43-48, with the physical meaning of the hemorrhagic illness, with the possible causes of the hemorrhage, with the social and religious implication of the illness. The work presents an exegetical interpretation of the text in focus, with its prerogatives of interpretation, with the analysis of textual variants and the literary analysis of the Gospel of Luke. The work also focuses on the initiative of the hemorrhagic woman and her cure through the miraculous action of Jesus. The work also reflects on the miracle of the cure and the cure as a miracle, about miracle in the Bible, in the Old and New Testament, and specifically about the miracle of the cure of the hemorrhagic woman and its physical and social meaning. Finally, the work lists a reasonable number of works where the readers and the researchers can obtain more information on the theme.